2011
DOI: 10.1002/jbmr.350
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ plays a role in bone formation in vivo and rescues osteoporosis in ovariectomized mice

Abstract: Interferon g (IFN-g) is a cytokine produced locally in the bone microenvironment by cells of immune origin as well as mesenchymal stem cells. However, its role in normal bone remodeling is still poorly understood. In this study we first examined the consequences of IFN-g ablation in vivo in C57BL/6 mice expressing the IFN-g receptor knockout phenotype (IFNgR1 À/À ). Compared with their wild-type littermates (IFNgR1 þ/þ ), IFNgR1 À/À mice exhibit a reduction in bone volume associated with significant changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 51 publications
5
118
0
1
Order By: Relevance
“…Although bone mass is decreased in Ifngr -/-mice, this appears to be primarily a defect in bone formation, and osteoclast number is not increased (49). Neither IFN-γ nor IFN-γR deficiency substantially affected BM OCP frequency or number (J.F.…”
Section: Discussionmentioning
confidence: 99%
“…Although bone mass is decreased in Ifngr -/-mice, this appears to be primarily a defect in bone formation, and osteoclast number is not increased (49). Neither IFN-γ nor IFN-γR deficiency substantially affected BM OCP frequency or number (J.F.…”
Section: Discussionmentioning
confidence: 99%
“…(1,3) An effective bone anabolic agent would induce bone formation by stimulating osteoblast activity, by protecting osteoblasts against premature death, and by promoting the differentiation of MSC down the osteoblast rather than the adipocyte lineage. (1) In fact, several studies have demonstrated that it is possible to stimulate osteoblast differentiation at the expense of adipogenesis using compounds such as parathyroid hormone, (18) interferon gamma, (19,20) and strontium ranelate. (21) The active metabolite of vitamin D, 1,25(OH) 2 D 3 , has also been shown to stimulate bone formation by promoting osteoblastogenesis (12) and inhibiting adipogenesis (17) in a murine model of age-related bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…When ovariectomized, sham-operated, and intact lactating rats were each stressed by a 0.1% calcium diet, there was no difference in the reduction of femoral ash weight among the groups (32). Ovariectomy to create estradiol deficiency leads to modest and slow bone loss in rodents, and not to the rapid loss that occurs during lactation (22,34,260). Conversely, treatment with estradiol to achieve fivefold higher levels than normal during lactation blunted bone loss and caused a small decline in milk calcium (956).…”
Section: Animal Datamentioning
confidence: 99%